Recent historiographical approaches to the process of independence in Argentina - Di Meglio, Gabriel Marco (History compass, 2019)
In the last decades, there was a substantial historiographical revision of the revolution of independence in what today is Argentina, which modified the traditional narratives about it. Recent historians have argued it's impossible to study Argentine Independence isolated from its context, as it used to be done. They also showed how independence was not planned or even desired but by very few people before 1810; it was not even the first goal of the majority of the revolutionaries that year. They have also established that there was not an Argentine national identity before the revolution and that it was constructed slowly after independence. And they also proved there was not only a small group of wealthy White men running the process but many other crucial actors as well. This paper examines briefly those statements and considers the revolutionary aspects of the process of independence, according to these recent contributions.